Pengaruh Rendaman Air Hangat Kencur Terhadap Edema Ekstremitas Bawah Ibu Hamil Trimester III - Diana Aulia Putri Handayani; Rani Safitri; Raden Maria Veronika Widiatrilupi (Universitas Ivet, 2026)
Lower extremity edema is a common complaint during the third trimester of pregnancy that can interfere with mobility and maternal comfort. A potential non-pharmacological therapy is warm water soaks mixed with sand ginger (Kaempferia Galanga), which possesses anti-inflammatory properties. Study aimed to analyze the effect of warm sand ginger water soaks on reducing the degree of lower extremity edema in third-trimester pregnant women. The research employed a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 47 respondents at TPMB Bd. Ratna Kurnianingtyas, S.ST, selected through purposive sampling. The intervention was administered for five consecutive days with a duration of 10-15 minutes per session. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that prior to the intervention, all respondents (100%) experienced edema. Following the five-day intervention, all respondents demonstrated a downward trend in edema degree, with 61.7% achieving a normal condition. Statistical analysis yielded a p-value of 0.000 (p < 0.05) with a Z-score of -6.164, indicating a very strong significant effect. Warm sand ginger water soak therapy is proven effective in reducing the degree of lower extremity edema in third-trimester pregnant women and is recommended as a safe and economical alternative for self-care.